Comparison of minimally invasive plate versus intramedullary nailing in the treatment of distal tibial metaphyseal fractures - Say, Ferhat; İnkaya, Erkan; Gürler, Deniz; Bülbül, Murat; Gültaç, Emre (Acta Medica Belgica, 2020)
Treatment was made by locked anatomic tibial plate with MIPO technique on 17 patients (Group1), closed intramedullary nailing on 18 patients (Group2). The cases were evaluated with the AFAS score.The median operation duration was 90(59-139)mins in Group1, 77.5(59-145)mins in Group2. The median union time was 15(11-20)weeks in Group1, 18(1222)weeks in Group2. The median AFAS score was 84(47-90) in Group1, 82(65-90) in Group2. The most common complication was infection in Group1 and malunion in Group2. Only the difference in operation time was found to be statistically significant between the two groupsThe clinical and functional results of both treatment methods were similar and effective. Malalignment should be kept in mind when treating with intramedullary nail; infection when treating with MIPO.
Keywords: Fracture; Distal Tibia; Intramedullary Nailing; Minimally Invasive Plate Osteosynthesis